2020
DOI: 10.1177/1073274820968914
|View full text |Cite
|
Sign up to set email alerts
|

Opa-Interacting Protein 5 Expression in Human Glioma Tissues Is Essential to the Biological Function of U251 Human Malignant Glioma Cells

Abstract: Opa-interacting protein 5 (OIP5) is a member of the cancer-testis antigen (CTA) family that elicits a spontaneous antitumor immune response. The failure of current immunotherapies for glioma has prompted the search for novel biomarkers that may be utilized as therapeutic targets. This study aimed to investigate whether OIP5 serves as a target for malignant glioma immunotherapy. Glioma specimens from 53 adult patients were evaluated for OIP5 expression by immunohistochemical (IHC) staining, and the correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…This search highlighted OIP5 as a protein associated with MISP. Notably, OIP5 has been previously reported to be highly expressed in various cancers, including CRC, hepatocellular carcinoma, renal cell carcinoma, bladder cancer, breast cancer, and glioma [ 33 , 34 , 35 , 36 , 37 , 38 ]. OIP5, also known as LINT-25, interacts with lamina-associated polypeptide 2α (LAP2α), a nuclear protein involved in chromatin binding during the cell cycle [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This search highlighted OIP5 as a protein associated with MISP. Notably, OIP5 has been previously reported to be highly expressed in various cancers, including CRC, hepatocellular carcinoma, renal cell carcinoma, bladder cancer, breast cancer, and glioma [ 33 , 34 , 35 , 36 , 37 , 38 ]. OIP5, also known as LINT-25, interacts with lamina-associated polypeptide 2α (LAP2α), a nuclear protein involved in chromatin binding during the cell cycle [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of genes in cancer lead to tumorigenesis [ 19 , 20 ]. Previous studies have shown that OIP5 is highly expressed in various human malignant tumors, such as breast cancer [ 10 ], malignant glioma [ 21 ], liver cancer [ 14 ], and bladder cancer [ 22 ], and can cause corresponding immune responses in tumor patients. Gong et al confirmed that OIP5 is related to the infiltration of T cells, B cells, macrophages and other immune cells in renal clear cell carcinoma and is a potential immunotherapeutic target for renal clear cell carcinoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Opa interacting protein 5 (OIP5) was discovered as an Opa (Neisseria gonorrhoeae opacity-associated) interacting protein [16]. The protein is highly enriched in human testis (https://www.proteinatlas.org/ENSG00000104147-OIP5/tissue, accessed on 1 August 2021) [17]; its upregulation is associated with adverse clinical features in multiple cancer types, including leukemia [18], ccRCC [19], glioma [20], and the cancers of the liver [21,22], lung [23], breast [24], gastric [25,26], and bladder [27][28][29][30]. Functionally, knockdown of OIP5 was reported to attenuate the proliferation of bladder cancer cells [29], as well as colorectal and gastric cells in vitro [25].…”
Section: Introductionmentioning
confidence: 99%